Desenvolvimento de método analítico para determinação da composição de aminoácidos em proteína de soja utilizando sistema SIA com pervaporação - Pedroso, Mirian Suellen Camargo (2014)
In this work is proposed the development and application of an analytical method using sequential injection analysis (SIA) and pervaporation to quantify amino acid in protein hydrolyzed. The quantitative determination of the amino acids was carried out by monitoring the CO2 released during ninhydrin derivatization reaction. The produced gas, converted to electrolyte, was monitored by electrochemical detector, and all the process steps were performed automatically by programed commands by computer. During validation the method it was proved to be linear, accurate and selective. The linearity was tested in the range of 0.5-3.5 mmol L-1, with R2 > 0.991. The repeatability presented rsd 4.83. The method was applied to analysis isolated amino acid in solution and in hydrolyzed crude of soybean protein, being this latter for determination of amino acid content of protein. The results obtained by the proposed method were compared to those obtained by Kjeldahl traditional method in the AAs quantitation in market soy protein concentrates and produced value close to aminoacids assay, 70.03 g/100 g and 72.79 g/100 g of sample, respectively. The time of quantification by SIA method was 5 min from the hydrolyzed protein